Kesejahteraan Psikologis Dewasa Awal:Tinjauan Sistematis Terhadap Faktor-Faktor Yang Mempengaruhi - Sela Meiliani; IGAA Noviekayati; Suhadianto Suhadianto (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Psychological well-being (PWB) has become a major concern among young adults who face various life demands. PWB significantly affects quality of life, academic achievement, and mental health, yet a comprehensive understanding of trends, causes, and its impacts among young adults over the past five years is still limited. This systematic review aims to identify factors influencing Psychological well-being in young adults and analyze its psychological implications from 2021–2026. Using a Systematic Literature Review (SLR) method based on PRISMA 2020, this study conducted a search on PubMed, Google Scholar, and Scopus. The keywords used included psychological well-being, young adults, influencing factors, and psychological well-being. The results showed that internal factors (Self-esteem, emotion regulation, mindfulness, optimism) and external factors (social support, family conditions, social environment) play a significant role in influencing PWB. Risk factors like loneliness and Fear of Missing Out (FoMO) are found to be negatively related to psychological well-being. Academic stress and early adult life pressures lead to significant psychological, cognitive-motivational, social behavior, well-being, and physiological consequences. These findings highlight the need for psychological interventions, stronger social support, and policies that support early adult mental health.